Endophytic Bacterial Community Structure and Function Response of BLB Rice Leaves After Foliar Application of Cu-Ag Nanoparticles - Weimin Ning; Mingxuan Li; Lei Jiang; Mei Yang; Maoyan Liu; Yong Liu (Nanomaterials)
Bacterial leaf blight (BLB) is a destructive disease caused by Xanthomonas oryzae pv. oryzae (Xoo). It has been proven that BLB adversely influences the growth and production of rice, resulting in substantial losses in yield. Nanoparticle–antimicrobial compounds possess excellent physicochemical properties, which have generated groundbreaking applications in protecting rice against BLB attacks. However, there is less research focused on the interaction between nanoparticles and the microbiome of BLB rice leaves, particularly the structure and function of endophytic bacteria, which are essential to plant health and pathogenesis. Therefore, the study explored how Cu-Ag nanoparticles influenced the endophytic bacteria’s composition and functions in healthy and BLB rice leaves. The data demonstrated that the relative abundance of beneficial bacteria, Burkholderiales, Micrococcales, and Rhizobiales, increased after the introduction of Cu-Ag nanoparticles on the leaves of BLB rice. The examination of PAL activity demonstrated that nanoparticles limited the spread of Xoo in rice leaves. Furthermore, endophytic community functional prediction demonstrated that nanoparticles may regulate the physiological process associated with potential stress resistance and growth-promoting function in the endophytic communities. This investigation may enhance the understanding of interactions between nanoparticles and the composition of rice endophytic microbiome, which can contribute to the exploration and application of nanomaterials in crop pathogen management.